A model for the biochemical degradation of inosine monophosphate in hake (Merluccius merluccius). (May 2017) - Vilas, C.; Alonso, A.A.; Herrera, J.R.; García-Blanco, A.; García, M.R.
Abstract: ATP-derived products are typically used as early indicators of fish quality loss during storage. In this work, we explore different biochemical routes that are potentially relevant in contributing to nucleotide degradation in hake ( Merluccius merluccius ). A major motivation of this study is to get more insight on the biochemical degradation mechanisms of nucleotide catabolites in hake muscle at fish storage and transport conditions. This requires the identification of its relevant pathways. To that purpose, different degradation routes proposed in the literature are considered and a mathematical model for the degradation process is derived. First order kinetics are assumed for all the reactions and temperature dependence is taken into account through the Arrhenius equation. Unknown model parameters, namely activation energies and pre-exponential Arrhenius coefficients, are estimated via fitting to experimental data. From the estimation results, relevant routes are identified. The kinetic study is performed on sterile fish juice to avoid coupling with microbial degradation mechanisms or possible interferences of the food matrix that might hide biochemical interactions. The proposed scheme adequately describes biochemical changes in nucleotide catabolites under variable temperature profiles. It also reveals a pathway which at least seems relevant for nucleotide degradation in hake. Highlights: We explore different biochemical routes for nucleotide degradation in fish. A mathematical model calibrated via parameter estimation is proposed. Quantitative evidence on the existence of alternative biochemical routes is provided. The model can be used to predict quality losses at the early stages of fish storage.